Neurofibromatosis type 1 is not associated with subarachnoid haemorrhage - Kurtelius A.; Kallionpää R.A.; Huttunen J.; Huttunen T.J.; Helin K.; Koivisto T.; Frosen J.; von und zu Fraunberg M.; Peltonen S.; Peltonen J.; Jääskeläinen J.E.; Lindgren A.E. (PUBLIC LIBRARY SCIENCE, 2022)
BackgroundThe prevalence of intracranial aneurysms (IAs) has been proposed to be elevated in the patients with neurofibromatosis type 1 (NF1). Our aims were to determine the prevalence of NF1 in a large Finnish population based cohort of IA patients and, on the other hand, the occurrences of subarachnoid haemorrhage and unruptured intracranial aneurysms in a nationwide population-based cohort of NF1 patients and its matched ten-fold control cohort.MethodsThe Kuopio IA Database (www.kuopioneurosurgery.fi) includes all ruptured and unruptured IA cases admitted to the Kuopio University Hospital (KUH) from its defined Eastern Finnish catchment population since 1980. In this registry-based study, we cross-linked the Kuopio IA database with the Finnish national registry covering all hospital diagnoses. The NF1 diagnoses of the 4543 patients with either saccular of fusiform IA were identified from 1969 to 2015 and verified from patient records. Our second approach was to analyze the occurrence of aneurysmal subarachnoid haemorrhage (aSAH) and unruptured IAs in a nationwide population-based database of 1410 NF1 patients and its ten-fold matched control cohort (n = 14030) using national registry of hospital diagnoses between 1987 and 2014.Results One NF1 patient was identified among the 4543 IA patients. Three verified IA cases (one unruptured IA and two aSAH cases) were identified in the cohort of 1410 NF1 patients, with similar occurrences in the control cohort.Conclusions We found no evidence in our population-based cohorts to support the conception that NF1 is associated with IAs. Our results indicate that the incidence of aSAH is not elevated in patients with NF1. Further studies are required to confirm that there is no association between NF1 and unruptured IAs.